2004
DOI: 10.1200/jco.2004.02.133
|View full text |Cite
|
Sign up to set email alerts
|

Matched-Pair Analysis of Survival of Never Smokers and Ever Smokers With Squamous Cell Carcinoma of the Head and Neck

Abstract: Survival differed significantly between never smokers and ever smokers with SCCHN. These results are not substantively explained by differences in cancer-associated symptoms or alcohol use, but the CIs are wide and some imprecision remains. Regardless, possible fundamental differences in SCCHN between ever smokers and never smokers may exist, and further molecular characterization of these tumors is needed to determine whether biologic differences needing targeted therapies exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 27 publications
3
62
0
2
Order By: Relevance
“…* This method was chosen because it accommodates a non-normal distribution of events, analysis of matched intervention-control pairs, and a large proportion of patients with missing data for the time of an event (many patients did not have a subsequent visit during the 365-day follow-up period). 16 The first step was to create a basic model. "Treatment" was the main covariate in this model; gender, race, reference year, and insurance status were added to control for their effects.…”
Section: Discussionmentioning
confidence: 99%
“…* This method was chosen because it accommodates a non-normal distribution of events, analysis of matched intervention-control pairs, and a large proportion of patients with missing data for the time of an event (many patients did not have a subsequent visit during the 365-day follow-up period). 16 The first step was to create a basic model. "Treatment" was the main covariate in this model; gender, race, reference year, and insurance status were added to control for their effects.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, head and neck cancer patients with any history of smoking (former or current) were found to have not only lower rates of survival but also lower rates of disease-specific survival and recurrence-free survival compared with patients who had never smoked. 28 In a study of patients with Stage I nonsmall-cell lung cancer, Fujisawa and colleagues 29 found a significantly higher overall survival rate at 10 years for patients reporting less than 30 pack-years of cigarette smoking (83.0%) than for patients with a history of more than 30 pack-years (36.7%).…”
Section: Impact Of Smoking and Smoking Cessation On Survival Ratesmentioning
confidence: 99%
“…These groups of patients need to be studied further, for the possible factors that induce molecular changes in the epithelium which may proceed to dysplasia and cancer. Some of the risk factors observed in the past are viral association particularly infection with Human papilloma virus (HPV), Infections with microorganism such as candida, Syphilis, Poor oral hygiene, Tooth loss due to aggressive periodontitis, And a diet low in fresh fruits and vegetables 8 . Prevalence ofHPV-16 is reportedbe high in Oral Squamous Cell Carcinoma and the data concerning the prevalence of HPV in the oral cavity is not similar, ranging from 2.6-98% 9 .…”
Section: Discussionmentioning
confidence: 99%